2021
DOI: 10.1016/j.cjco.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Delays in ST-Elevation Myocardial Infarction Care During the COVID-19 Lockdown: An Observational Study

Abstract: Background: Management of ST-elevated myocardial infarction (STEMI) necessitates rapid reperfusion. Delays prolong myocardial ischemia and increase the risk of complications, including death. The COVID-19 pandemic may have affected management of STEMI. We evaluated the relative volume of hospitalizations and clinical time intervals within a regional STEMI system. Methods: Four hundred ninety-four patients with STEMI were grouped into prelockdown, lockdown, and reopening cohorts. Clinical, temporal, and outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Furthermore, there was a significant increase in time from FMC-to-STEMI diagnosis and FMCto-reperfusion time. These findings point to delays in in-hospital processes related STEMI care J o u r n a l P r e -p r o o f which are supported by a large systematic review and meta-analysis by Rattka et al 10 Similar findings have been previously reported in observational studies around the world, 4,8,9,[14][15][16][17][18][19] including a recently published Canadian study by Clifford et al, who described STEMI care in an Ontario population during the COVID-19 pandemic. 14 Our results were discrepant with previously reported studies as we did not find that there was a significant reduction in patients presenting with STEMI during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, there was a significant increase in time from FMC-to-STEMI diagnosis and FMCto-reperfusion time. These findings point to delays in in-hospital processes related STEMI care J o u r n a l P r e -p r o o f which are supported by a large systematic review and meta-analysis by Rattka et al 10 Similar findings have been previously reported in observational studies around the world, 4,8,9,[14][15][16][17][18][19] including a recently published Canadian study by Clifford et al, who described STEMI care in an Ontario population during the COVID-19 pandemic. 14 Our results were discrepant with previously reported studies as we did not find that there was a significant reduction in patients presenting with STEMI during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 62%
“…A total of 32 studies met our inclusion criteria. Four studies each originated from China, 4,24,32,33 Italy, 20,[34][35][36] and North America, [37][38][39][40] 3 each from France [41][42][43] and Turkey, [44][45][46] 2 from the United Kingdom, 47,48 and 1 each from Austria, 49 Belgium, 50 Egypt, 51 Iran, 52 Israel, 53 Japan, 54 Pakistan, 55 Poland, 56 Singapore, 23 Spain, 57 and Switzerland. 60 One study was a multicentred cohort study of various databases belonging to different European countries.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…5,6,13,14 Several studies have shown a significant decline in the number of patients seeking emergency care for cardiac events during the pandemic, citing hesitancy or fear as the main cause. [15][16][17] This trend is supported by data showing that Canadian emergency department volumes dropped by 50% during March and April, 2020. 18 Some of the excess mortality may also be a result of delayed or deferred surgical procedures.…”
Section: Discussionmentioning
confidence: 74%